Rainfall-induced shallow landslide volume estimation using robust empirical-statistical models - Seray, Franco
Volume is a vital factor in landslide assessments. To estimate the parameter in the immediate aftermath of the disaster, empirical-statistical models are generated for landslide inventory of Ormoc, Leyte. With the dataset from UP NOAH, the parameters - volume, surface area, and maximum elevation - are derived from digital elevation models ASTER of NASA, and SAR of UP DREAM. Using robust linear regession to correlate data points, models are created and used for volume estimates with corresponding relative error from specified volume in the inventory. The inventory is found to be best estimated by the equation e7.1725x0.9341.